2021
DOI: 10.1155/2021/6390530
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Association between Diabetes Mellitus and Traditional Chinese Medicine Constitution

Abstract: Objective. To explore the distribution of constitution types of diabetes mellitus (DM) in traditional Chinese medicine (TCM) and to provide evidence-based medicine basis for the prevention and treatment of diabetes. Methods. PubMed, Embase, Web of Science, and three Chinese databases were searched to include research literature on the relationship between diabetes and TCM constitution. The single rate study of cross-sectional literature was conducted with RStudio software, and the control meta-analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Therefore, the PDC was one of the common types of TCMC in the Lingnan area. The PDC has been shown to be a high-risk factor for several chronic metabolic diseases, such as hyperlipidemia, DM, and NAFLD [ 14 , 34 , 35 ], and is considered to be a “common soil” for endocrine, nutritional, and metabolic diseases [ 35 ]. Based on TCM theory, MAFLD is caused mainly by the interaction of the PDC and abnormal function of the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the PDC was one of the common types of TCMC in the Lingnan area. The PDC has been shown to be a high-risk factor for several chronic metabolic diseases, such as hyperlipidemia, DM, and NAFLD [ 14 , 34 , 35 ], and is considered to be a “common soil” for endocrine, nutritional, and metabolic diseases [ 35 ]. Based on TCM theory, MAFLD is caused mainly by the interaction of the PDC and abnormal function of the liver and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the distribution of TCM constitution in people with high-normal BP was different from other diseases, such as diabetes mellitus, and dyslipidemia. Yin -deficiency constitution, phlegm-dampness constitution, and Qi -deficiency constitution were the common constitution types of diabetic people [ 42 ], the top three TCM constitutions of dyslipidemia were phlegm-dampness constitution, Qi -deficiency constitution, and Yang -deficiency constitution [ 43 ], these indicated that there were differences in the distribution of TCM constitutions among different diseases. Professor Sun pointed out that from health to pro-disease, the fundamental reason lies in constitution changes, and that the biased constitution was the internal basis of pre-disease [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common constitution of people with high-normal BP in South China was the phlegm-dampness constitution, while the most common constitution in North China was the Yang -deficiency constitution, which may be related to the climatic characteristics of different regions. The climate in South China is warm and humid, and residents are easy to generate phlegm, and dampness, which may lead to more people with phlegm-dampness [ 42 ]. However, the climate in North China is cool and dry, which may not easily generate phlegm or dampness, thus having less influence on the health of residents [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical presentations, TCM constitution could be categorized as nine types: inherited special constitution, balance constitution, blood stasis constitution, damp-heat constitution, yin-deficiency constitution, phlegm-dampness constitution, qi-stagnation constitution, qi-deficiency constitution, and yang-deficiency constitution [20]. Because of the clinical correlation between phlegm-dampness constitution with GLMD, scientific studies of phlegm-dampness constitution have attracted the keen interest of many research groups globally [21]. Based on these findings, we hypothesized that the intervention of phlegmdampness constitution might provide a novel strategy to treat GLMD.…”
Section: Discussionmentioning
confidence: 99%